DEVELOPMENT AND EVALUATION OF BIODEGRADABLE PACKAGING FROM THE ARYL OF THE FRUIT OF Hymenaea stigonocarpa - Antonio Carlos Pereira de Menezes Filho (Revista de Agricultura Neotropical, 2022)
The fruits of Hymenaea stigonocarpa have a sweet, starchy fibrous structure used as food among wild animals and man in the field. In the present study, the physical, physicochemical, optical, microstructural, and antibacterial properties of aryl (H. stigonocarpa) film were investigated. The amylaceous solution was obtained from the aryl of H. stigonocarpa, the biodegradable film was prepared according to the casting technique. The physicochemical characteristics for thickness (mm), humidity (%), water solubility (%), biodegradability time, and transmittance (T%) were evaluated. Morphology by optical micrographic, and scanning electron, mathematical modeling in 3D, and for the mechanical parameters of tensile strength, maximum tension, elongation, and elasticity module, and biological properties on antibacterial activity (Staphylococcus aureus, Escherichia coli and Enterococcus faecalis). The results obtained for the biodegradable film were a brown-yellow color, aroma, and homogeneity, thickness 0.27 mm, humidity 12.45%, solubility in water 57.48%, the biodegradability of 100%, maximum and minimum transmittance 82.25, and 1.32 (T%), in the optical micrograph small imperfections were observed, and in the scanning electron micrograph small cracks. The mathematical modeling in 3D presented a surprising result, which is an important device in the aid of imaging. The mechanical characteristics for maximum tension 3.17 N, rupture stress 1.34 MPa, elongation 2.99% and elasticity with 90.07 MPa presented satisfactory results comparable to other biodegradable films of native starch. The bioactive film of the aryl (H. stigonocarpa) showed antibacterial activity against Staphylococcus aureus 7 mm, Escherichia coli 5 mm, and Enterococcus faecalis 8 mm. Biodegradable packaging from Hymenaea stigonocarpa aryl has great potential for use as a food packaging.